European norms in transit: trade mark norms, TTIP uncertainties and the relevance of TPP. - Firth, Alison (Asia Europe Journal, 2015)
Previous research has demonstrated that EU trade mark norms found their way into New Zealand law through the World Trade Organisation agreement on Trade-Related Aspects of Intellectual Property Rights (WTO TRIPS). This paper will give a brief résumé of that research and outline the current enquiry-whether these and related norms are likely to be re-transmitted, in identical or modified form. This could occur via the draft intellectual property chapter of the proposed Trans-Pacific Partnership (TPP) agreement. While this was under discussion, the EU and USA were negotiating a Trans-Atlantic Trade and Investment Partnership (TTIP) agreement. Although geographical indications (GIs, protected under trade mark law in the USA) have been a hot topic in TTIP negotiations, there is scant information on any possible chapter on GIs, trade marks and other forms of intellectual property in TTIP. However, US Trade Representative and TTIP negotiator Michael Froman has spoken admiringly of the intellectual property provisions in the draft TPP. If an intellectual property chapter were introduced into TTIP, it seems likely that TPP text would be adopted or adapted, bringing norms full circle back to the EU. In considering this possibility, it is suggested that the biological analogy of viral transfer of genetic code may be even more apt than that of transplants to illuminate the process of re-transmission of adopted or adapted legal norms through the medium of international treaties.